Analysis of beta-thalassemia mutations in northern Thailand using an automated fluorescence DNA sequencing technique - Sirichotiyakul S. (2014)
A total of 218 beta-thalassemia (thal) genes from 109 beta-thal major patients were characterized using an automated fluorescence DNA sequencing technique. Eight different mutations were identified in all 218 alleles (100%). Four common mutations accounted for 96.8% [49.5% were codons 41/42 (-TTCT), 34.4% were codon 17 (A --> T), 6.9% were IVS-I-1 (G --> T) and, 6.0% were codons 71/72 (+A)]. There were three cases of -28 (A --> G) and one of IVS-II-654 (C --> T), mutations that have been previously described in Thai subjects. We also identified two mutations in the beta-globin promoter region which have not been reported in Thailand before [-31 (A --> G) and -87 (C --> A)]. Although these mutations are described as beta+-thal, the compound heterozygote with one of the common beta(o)-thal mutations exhibits the phenotype of beta-thal major. The frequency of beta-thal genes in northern Thailand were similar to the northeastern region, but different from those reported in southern and central Thailand, where IVS-I-5 (G --> C) and IVS-II-654 (C --> T) were the second most common anomalies, respectively. The spectrum of beta-globin gene mutations from this study will be useful for planning a prenatal diagnosis program especially for this region of Thailand.